β-elemene down-regulates HIF-lα, VEGF and iNOS in human retinal pigment epithelial cells under high glucose conditions - Zhou, Yun (Int J Ophthalmol, 2020)
AIM: To investigate the effects and mechanism of β-elemene on the expressions of hypoxia-inducible factor-1α (HIF-lα), vascular endothelial growth factor (VEGF) and inducible nitric oxide synthase (iNOS) in human retinal pigment epithelial (RPE) cells under high glucose conditions. METHODS: ARPE-19 cell line was cultured under eight conditions: 1) low glucose (LG; 5.5 mmol/L); 2) high glucose (HG; 33 mmol/L); 3) high glucose with 20 µg/mL β-elemene (HG+20E); 4) high glucose with 40 µg/mL β-elemene (HG+40E); 5) high glucose with SB203590 [HG+SB203590, p38-mitogen-activated protein kinase (p38-MAPK) pathway inhibitor]; 6) high glucose with LY294002 [HG+LY294002, phosphoinositide 3-kinase/protein kinase B (PI3K/Akt) pathway inhibitor]; 7) high glucose with 40 µg/mL β-elemene and SB203590 (HG+40E+SB203590); and 8) high glucose with 40 µg/mL β-elemene and LY294002 (HG+40E+LY294002). Cells were treated in conditions 1-4 for 24 and 48h, while for 48h in conditions 5-8. Then mRNA and protein levels of HIF-1α, VEGF and iNOS in cells were measured by real-time polymerase chain reaction (qPCR), immunofluorescence and Western blotting, respectively. Furthermore, protein levels of total p38-MAPK, phosphorylated p38-MAPK (p38-MAPK-P), total Akt and phosphorylated Akt (Akt-P) in cells of conditions 2 and 4 which treated for 48h were measured by Western blotting. RESULTS: The mRNA levels and protein levels of HIF-1α, VEGF and iNOS in cells were significantly reduced in conditions 3-8 when compared with those in condition 2 (P<0.05). These reductions were more obvious in conditions treated for 48h than in conditions treated for 24h. The protein levels of p38-MAPK-P and Akt-P in cells of condition 4 were significantly lower than in condition 2 (P<0.01). CONCLUSION: β-elemene down-regulates HIF-1α, VEGF and iNOS in ARPE-19 cells under a high glucose condition. The inhibitory effect of β-elemene is more significant when its concentration and treatment time are increased, as well as it is combined with SB203590 or LY294002 treatment. P38-MAPK and PI3K/Akt signaling pathways may play a role in this inhibitory effect.